Evaluation of pressed shredded empty fruit bunch (EFB)-palm oil mill effluent (POME) anaerobic sludge based compost using Fourier transform infrared (FTIR) and nuclear magnetic resonance (NMR) analysis - Samsu Baharuddin, Azhari; Abdul Rahman, Nor'aini; Md. Shah, Umi Kalsom; Hassan, Mohd Ali; Wakisaka, Minato; Shirai, Yoshihito (Academic Journals, 2011)
Pressed-shredded empty fruit bunches (EFB) and palm oil mill effluent (POME) anaerobic sludge from a 500 m3 closed anaerobic digester system was utilized for the co-composting treatment. Scanning electron microscopy (SEM) analysis showed that the shredding-pressing treatment on EFB gave better results in removing the debris and silica bodies as compared to only shredding treatment. However, similar characteristics were detected in both physically-treated EFB samples by Fourier transform infrared (FTIR) analysis, mainly in the regions of 900 to 1740 and 2800 to 3400 cm-1. After the anaerobic digestion of fresh raw POME, the protein origin (Amide I) band appeared in the POME anaerobic sludge. Besides, the band intensities at 2925 and 2855 cm-1 which attributed to the composition of fat and lipid was decreased. The maturity of the composting material after 40 days of treatment was detected by the appearance of the nitrate band at 1376 cm-1 and the results corresponded to the final C/N ratio of 12.4. Solid state 13C CP/MAS nuclear magnetic resonance (NMR) was also used to reveal the characteristic changes of pressed-shredded EFB-POME anaerobic sludge based compost.